2018
DOI: 10.1163/15685411-00003180
|View full text |Cite
|
Sign up to set email alerts
|

A survey investigating the diversity and distribution of entomopathogenic nematodes in the UK and the first confirmed UK record of Steinernema carpocapsae

Abstract: Summary Entomopathogenic nematodes (EPN) of the families Steinernematidae and Heterorhabditidae are lethal insect parasites that have been commercialised as biological control agents. EPN have been isolated from across the world but it has been more than 20 years since the last survey of the UK, and species like Steinernema carpocapsae have never been found here and positively identified through molecular biology. We collected 518 soil samples from a diverse range of habitats across the UK and baited them with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…To address the knowledge gap, we conducted a survey of the biodiversity and distribution of EPN fauna in Yunnan province by collecting 789 soil samples from 232 sites during 2017 and 2018. The major objectives of the present study were (i) to investigate the natural occurrence of indigenous EPNs in the entire Yunnan province by standard genotyping procedures ( Al-Zaidawi et al, 2019 ; Edmunds et al, 2018 ), and (ii) to test the virulence of the detected indigenous EPNs isolates against S. litura.…”
mentioning
confidence: 99%
“…To address the knowledge gap, we conducted a survey of the biodiversity and distribution of EPN fauna in Yunnan province by collecting 789 soil samples from 232 sites during 2017 and 2018. The major objectives of the present study were (i) to investigate the natural occurrence of indigenous EPNs in the entire Yunnan province by standard genotyping procedures ( Al-Zaidawi et al, 2019 ; Edmunds et al, 2018 ), and (ii) to test the virulence of the detected indigenous EPNs isolates against S. litura.…”
mentioning
confidence: 99%
“…Thurston et al (1994) even found that H. bacteriophora virulence was enhanced by low levels of salinity but higher concentrations affected survival. Our most salinity-tolerant strain was S. glaseri 367, which was the only EPN isolate from an extensive survey of Lundy Island (Edmunds et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Service (1977) reported finding larvae of Ochlerotatus cantans infected with several nematodes, but these were unidentified mermithids and not EPNs. To investigate this further we used G. mellonella baiting of several samples from the Little Neston area collected in a previous study (Edmunds et al 2018) but found no EPNs, likely due to unsuitability of the heavy clay substrate of this habitat for EPNs (Kung et al 1990). Therefore, it seems O. detritus may not come into contact with EPNs frequently, and perhaps therefore has not evolved defences against them, making them particularly susceptible to attack.…”
Section: Discussionmentioning
confidence: 99%